f(x)f(a)⇒c0=c0+c1(x−a)+c2(x−a)2+c3(x−a)3+c4(x−a)4+⋯=c0+0+0+0+0+⋯=f(a)
f(1)(x)f(1)(a)⇒c1=1c1+2c2(x−a)+3c3(x−a)2+4c4(x−a)3+⋯=1c1+0+0+0+⋯=1f(1)(a)
f(2)(x)f(2)(a)⇒c2=(2⋅1)c2+(3⋅2)c3(x−a)+(4⋅3)c4(x−a)2+⋯=(2⋅1)c2+0+0+⋯=2⋅1f(2)(a)
f(3)(x)f(3)(a)⇒c3=(3⋅2⋅1)c3+(4⋅3⋅2)c4(x−a)+⋯=(3⋅2⋅1)c3+0+⋯=3⋅2⋅1f(3)(a)
⟹cn=n!f(n)(a)
f(x)=n=0∑∞cn(x−a)n⟹f(x)=n=0∑∞n!f(n)(a)(x−a)n
#Calculus
Easy Math Editor
This discussion board is a place to discuss our Daily Challenges and the math and science related to those challenges. Explanations are more than just a solution — they should explain the steps and thinking strategies that you used to obtain the solution. Comments should further the discussion of math and science.
When posting on Brilliant:
*italics*
or_italics_
**bold**
or__bold__
paragraph 1
paragraph 2
[example link](https://brilliant.org)
> This is a quote
\(
...\)
or\[
...\]
to ensure proper formatting.2 \times 3
2^{34}
a_{i-1}
\frac{2}{3}
\sqrt{2}
\sum_{i=1}^3
\sin \theta
\boxed{123}
Comments
@Gordon Chan If you have just learnt about this, then here's an interesting question.......How would you find the Taylor expansion of cotx centered at x=0
Log in to reply
Cotangent has an asymptote at x = 0 so I don't think that would work
you couldn't, but you could find the Taylor series of xcot(x) centered at 0, and play around with that to get a series for cot(x)
Log in to reply
Yeah......that was exactly what I had in mind......